Synthesis of 5-oxyquinoline derivatives for reversal of multidrug resistance - Dittrich, Torsten; Hanekop, Nils; Infed, Nacera; Schmitt, Lutz; Braun, Manfred (Beilstein Journal of Organic Chemistry, 2012)
The inhibition of ABC (ATP binding cassette) transporters is considered a powerful tool to reverse multidrug resistance. Zosuquidar featuring a difluorocyclopropyl-annulated dibenzosuberyl moiety has been found to be an inhibitor of the P-glycoprotein, one of the best-studied multidrug efflux pumps. Twelve 5-oxyisoquinoline derivatives, which are analogues of zosuquidar wherein the dibenzosuberyl-piperazine moiety is replaced by either a diarylaminopiperidine or a piperidone-derived acetal or thioacetal group, have been synthesized as pure enantiomers. Their inhibitory power has been evaluated for the bacterial multidrug-resistance ABC transporter LmrCD and fungal Pdr5. Four of the newly synthesized compounds reduced the transport activity to a higher degree than zosuquidar, being up to fourfold more efficient than the lead compound in the case of LmrCD and about two times better for Pdr5.
Keywords: acetals; enantiopure compounds; heterocycles; inhibitor; multidrug resistance